PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA INOVASI DENGAN GROWTH OPPORTUNITY SEBAGAI VARIABEL KONTROL (Studi Kasus Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022) - Agustin, Herliza; Awaluddin, Awaluddin (Ensiklopedia of Journal, 2025)
This study was conducted with the aim of providing empirical evidence of the influence of corporate governance mechanisms  on innovation performance with growth opportunities as a control variable with empirical studies on companies listed on the IDX for the 2019-2022 period. The population of this study is 9 sub-sectors of companies listed on the Indonesia Stock Exchange in 2019-2022. The sampling technique used is using the purposive sampling method where there are 19 companies. The hypothesis in this study is tested through the Outer Model and Inner Model with the help of WarpPLS software v 7.0. The results of this study are that the influence of the independent board of commissioners and institutional ownership has a positive and significant effect on innovation performance, managerial ownership has a negative and significant effect on innovation performance, and growth ooprtunity has a positive and significant effect on innovation performance.Keywords: Independent Board of Commissioners, Managerial Ownership, Institutional Ownership, Growth opportunity